2011
DOI: 10.2174/1874294701105010009
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Dehydrins in Oleae europaea Plants Exposed to Stress

Abstract: Dehydrins (DHNs) belong to a large family of proteins whose expression is associated with dehydration during seed maturation, pollen grain development and bud dormancy during winter, as well as plant adaptive response to various stressors. However, the exact roles played by different members of this protein family have not been fully defined. To gain a better understanding of DHN functions in olive plants, we used Western blot analyses to investigate their expression in the leaves of olive plants subjected to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 61 publications
1
15
0
Order By: Relevance
“…Our results suggest that dehydrin polypeptides of 16 and 23 kDa play a role in drought tolerance of bermudagrass. The function of 16 kDa for drought tolerance in our study is consistent with other findings in wheat [Triticum durum (Labhilili et al, 1995)] and olive [Oleae europaea (Tripepi et al, 2011)]. Lopez et al (2003) found that expression of a 24-kDa dehydrin was observed in some drought-tolerant wheat (Triticum aestivum) cultivars after 4 d of drought stress and positively associated with drought tolerance in wheat.…”
Section: Responses Of Volumetric Soil Watersupporting
confidence: 92%
“…Our results suggest that dehydrin polypeptides of 16 and 23 kDa play a role in drought tolerance of bermudagrass. The function of 16 kDa for drought tolerance in our study is consistent with other findings in wheat [Triticum durum (Labhilili et al, 1995)] and olive [Oleae europaea (Tripepi et al, 2011)]. Lopez et al (2003) found that expression of a 24-kDa dehydrin was observed in some drought-tolerant wheat (Triticum aestivum) cultivars after 4 d of drought stress and positively associated with drought tolerance in wheat.…”
Section: Responses Of Volumetric Soil Watersupporting
confidence: 92%
“…Dehydrin proteins (DHNs) are characteristic of such proteins, and confer outstanding ability to resist stress during periods of drought and salinity stress as well as in cold environments (Close et al, 1989; Porat et al, 2004; Rorat et al, 2006; Tripepi et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Lee et al (2005) found that the expression of rice OsDhn1 was associated with salinity and other abiotic stresses. Tripepi et al (2011) also reported 2 DHNs (40 kDa and 42 kDa) in association with salinity stress in olives. Furthermore, DHNs are highly influential in salinity stress tolerance in Physcomitrella patens (Ruibal et al, 2012) and Suaeda asparagoides (Ayarpadikannan et al, 2012).…”
Section: Discussionmentioning
confidence: 84%
“…They play a fundamental role in plant response and adaptation to multiple abiotic stresses (Hanin et al, 2011). DHNs were found to be associated with drought stress in olives (Tripepi et al, 2011), with osmotic stress in tea (Paul and Kumar, 2013) and with salt stress in Physcomitrella patens (Ruibal et al, 1012) and tomatoes (Muñoz-Mayor et al, 2012). In addition, they were found associated with cold stress in soybean (Yamasaki et al, 2013) and spinach (Chen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%